291 Ticagrelor monotherapy after percutaneous coronary intervention in high-risk patients with prior myocardial infarction: a prespecified twilight substudy. (8th December 2021) - Chiarito, Mauro; Cao, Davide; Baber, Usman; Pivato, Carlo; Briguori, Carlo; Sardella, Gennaro; Stefanini, Giulio; Dangas, George; Pocock, Stuart; Mehran, Roxana
Abstract: Aims: Patients with history of myocardial infarction (MI) undergoing percutaneous coronary intervention (PCI) remain at risk of recurrent ischaemic events. The optimal antithrombotic strategy for this cohort remains debated. Methods and results: In this prespecified analysis of the TWILIGHT trial, we evaluated the impact of prior MI on treatment effect of ticagrelor monotherapy vs. ticagrelor plus aspirin in patients undergoing PCI with at least one clinical and one angiographic high-risk feature and free from adverse events at 3 months after the index PCI. The primary endpoint was Bleeding Academic Research Consortium (BARC) type 2, 3, or 5, the key secondary endpoint was the composite of all-cause death, MI, or stroke, both at 12 months after randomization. 1937 (29.7%) patients with and 4595 (70.3%) without prior MI were randomized to ticagrelor and placebo or ticagrelor and aspirin. Patients with prior MI had increased rates of death, MI or stroke (5.7 vs. 3.2%, P  < 0.001) but similar BARC 2–5 bleeding (5.0 vs. 5.5%, P  = 0.677). Ticagrelor monotherapy reduced the risk of BARC 2–5 bleeding in patients with [3.4% vs. 6.7%; hazard ratio (HR): 0.50; 95% confidence interval (CI): 0.33–0.76] and without prior MI [4.2% vs. 7.0%; HR: 0.58; 95% CI: 0.45–0.76; p interaction = 0.54). Rates of the key secondary ischaemic outcome were similar between treatment groups irrespective of history of MI (prior MI: 6.0% vs. 5.5%; HR: 1.09; 95% CI: 0.75–1.58; no prior MI: 3.1% vs. 3.3%; HR: 0.92; 95% CI: 0.67–1.28; p interaction = 0.52). Conclusions: Ticagrelor monotherapy is associated with significantly lower risk of bleeding events as compared to ticagrelor plus aspirin without any compromise in ischaemic prevention among high-risk patients with history of MI undergoing PCI.